2009
DOI: 10.1007/s11249-009-9408-8
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion of Diamond-Like Carbon Deposited on Ti6Al4V

Abstract: Tribological and corrosion properties of Ti6Al4V alloy both bare and coated by diamond-like carbon (DLC) were investigated in PBS solution. The films obtained by a PACVD technique present high hardness, good corrosion and wear resistance and lower friction coefficient compared to bare alloy. Tribocorrosion tests on bare alloy showed that when wear stops, the alloy rapidly passivates. DLC films present superior wear resistance under dry conditions. However, film life is greatly reduced during tribocorrosion tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…DLC films have been caught more attention owing to their industrial applications such as excellent mechanical and tribological performance [4][5][6]. However, the true DLC films are very hard with high internal stresses, which tend to be brittle, have poor adhesion, and become unsuitable for highly loaded applications.…”
Section: Introductionmentioning
confidence: 99%
“…DLC films have been caught more attention owing to their industrial applications such as excellent mechanical and tribological performance [4][5][6]. However, the true DLC films are very hard with high internal stresses, which tend to be brittle, have poor adhesion, and become unsuitable for highly loaded applications.…”
Section: Introductionmentioning
confidence: 99%
“…As corrosion is mostly a surface phenomenon, the corrosion resistance is closely related to the composition and structure of surface films on metals [23][24][25][26]. In many tribological systems the materials forming the tribological contact are exposed to a corrosive environment and therefore they are subjected to both mechanical and chemical solicitations [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand both DLC coated substrates presented significant low COF both in dry wear and tribocorrosion; the rubbing action can generate a graphitic carbon layer that can be accumulated within the contact forming a transfer layer. This layer can, act as a solid lubricant during sliding wear (Manhabosco et al, 2009). In addition a very low wear rate was measured for both DLC coatings under dry and tribocorrosion tests.…”
Section: Discussionmentioning
confidence: 99%
“…The tribocorrosion performance of DLC coatings have been investigated in different conditions. Manhabosco et al (2009) indicated the DLC-Ti6Al4V obtained by PACVD presented superior wear resistance but decreased durability in the tribocorrosion test, which is caused by the loss of adhesion between the substrate and the coating due to the porosity of the DLC coating and the rise in the load (16 N, corresponding to 1.07 GPa mean contact pressure against alumina ball). Azzi et al (2009; pointed out the tribocorrosion performance of the DLC-stainless steel system were largely affected by the adhesion strength between the coating and the substrate, which is further determined by the proper interfacial bonding layer.…”
Section: Introductionmentioning
confidence: 99%